(untitled) (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Every child has the right to grow up in a safe and loving environment, but not all are granted such a privilege. IZ, a 15-year-old boy living at the Ora Et Labora Orphanage in Medan, experienced psychological trauma due to bullying during his early school years. This led to low self-esteem and social withdrawal. This field practice aimed to assist the client using a qualitative method with a single case study approach. The intervention process applied individual casework through several stages, including assessment, planning, implementation of creative and interpersonal sessions, and termination. The results showed improvement in the client’s confidence to express himself, social engagement, and self-belief. This assistance process demonstrates that empathetic and reflective-based interventions can support psychological recovery in children who have been victims of bullying.